2020
DOI: 10.15252/emmm.201911659
|View full text |Cite
|
Sign up to set email alerts
|

FBXL 4 deficiency increases mitochondrial removal by autophagy

Abstract: Pathogenic variants in FBXL 4 cause a severe encephalopathic syndrome associated with mt DNA depletion and deficient oxidative phosphorylation. To gain further insight into the enigmatic pathophysiology caused by FBXL 4 deficiency, we generated homozygous Fbxl4 knockout mice and found that they display a predominant perinatal lethality. Surprisingly, the few surviving animals are apparently normal until t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 53 publications
2
57
0
Order By: Relevance
“…Although proteins of this family participate in Skp1-cullin1-F-box (SCF)-dependent proteasomal ubiquitin-dependent protein catabolic process, FBXL4 has also been associated with mitochondrial dynamics [ 106 ]. However, studies conducted in Fbxl4 knockout mice have revealed that the molecular phenotype caused by FBXL4 mutations (mtDNA depletion observed in patients [ 45 ]) may be mediated by a global decrease in mitochondrial content due to the dysregulation of autophagy rather than a primary dysfunctional mtDNA maintenance [ 114 ]. C1QBP (complement component 1 Q subcomponent-binding protein) is a mitochondrial matrix protein of unknown function which is thought to be involved in inflammation and mitochondrial ribosome synthesis.…”
Section: Mitochondrial Dna Depletion and Multiple Deletions Syndromes (Mdds)mentioning
confidence: 99%
“…Although proteins of this family participate in Skp1-cullin1-F-box (SCF)-dependent proteasomal ubiquitin-dependent protein catabolic process, FBXL4 has also been associated with mitochondrial dynamics [ 106 ]. However, studies conducted in Fbxl4 knockout mice have revealed that the molecular phenotype caused by FBXL4 mutations (mtDNA depletion observed in patients [ 45 ]) may be mediated by a global decrease in mitochondrial content due to the dysregulation of autophagy rather than a primary dysfunctional mtDNA maintenance [ 114 ]. C1QBP (complement component 1 Q subcomponent-binding protein) is a mitochondrial matrix protein of unknown function which is thought to be involved in inflammation and mitochondrial ribosome synthesis.…”
Section: Mitochondrial Dna Depletion and Multiple Deletions Syndromes (Mdds)mentioning
confidence: 99%
“…Furthermore, a recent study showed that SKP2, another well-characterized F-box protein, regulated the stability of IDH1/2, the key TCA cycle enzymes, and SKP2 knockdown promoted the TCA cycle by reducing glycolysis [ 51 ]. Other studies revealed that FBXL7 and FBXL4 modulated mitochondrial morphology and function through survivin and other uncharacterized substrates [ 52 56 ]. FBXO7 and FBXO11 (also characterized as a NEDD8 E3) were shown to regulate mitochondrial morphology and function, as well as mitochondrial elimination by modulating PARP activation, apoptosis, and mitophagy, respectively [ 57 59 ].…”
Section: Mitochondrial Regulation By Neddylation Substrates and Crlsmentioning
confidence: 99%
“…Modulation of mitophagy may comprise a therapeutic strategy in mitochondrial diseases ( 131 , 132 ). Mitophagy can be stimulated by drugs such as the antibiotic actinonin ( 133 ) or the anti-diabetic metformin ( 134 ).…”
Section: Manipulating Mtdna In Cellsmentioning
confidence: 99%
“…Caloric restriction may extend lifespan in part by effects on mitophagy ( 136 ). Conversely, increased mitophagy may also be involved in mitochondrial diseases ( 132 ). Reactive oxygen species may also affect mitophagy and impact many diseases and the aging process ( 136 ).…”
Section: Manipulating Mtdna In Cellsmentioning
confidence: 99%